The Teaching About De Facto States in Times of Crises: The Case of Transnistria - Kosienkowski, Marcin (Roczniki Nauk Społecznych, 2024)
In this article, I share my personal experience of teaching about the de facto state of Transnistria during times of crises and within Central and East European and multicultural contexts. I begin by explaining where and when I teach about Transnistria, which may not be so obvious because it is a narrow topic. Next, I focus on how I approach classes devoted to Transnistria as a controversial and sensitive issue that requires specific teaching strategies. Finally, I discuss the outcomes of implementing these strategies and share my personal feelings about instruction concerning Transnistria. This article may be valuable to junior scholars who have recently started covering the subject of Transnistria and other de facto states and are seeking guidance. It may also benefit experienced senior scholars by offering them an opportunity to compare their teaching strategies.